2016
DOI: 10.1515/sjps-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Strategic voting in the 2011 and 2015 Polish Senate elections: Testing Duvergerʼs Law in the second-order elections

Abstract: This article tests Duverger's law through analysis of the Polish Senate elections in 2011 and 2015. These two elections were held under the new first-past-the-post (or single-member plurality) system, which replaced formerly used unlimited vote. The main aim of the article is to test, whether we can confirm the expectations of strategic voting in the context of the so-called second-order elections, as the Polish Parliament is a classical example of the asymmetrical bicameralism, with the secondary role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Furthermore, Tavits and Annus (2006) emphasized the role of democratic experience in new democracies of Eastern Europe and Russia when they convincingly demonstrated that strategic voting in third-wave democracies tends to increase as voters (but also political elites) become more experienced with the electoral process, the so-called ‘learning hypothesis’ (cf. Tavits and Annus, 2006: 80–87; Maškarinec, 2016). Similarly, Raymond et al (2016) confirmed that the effects of electoral systems and social cleavages significantly differ between emerging and established democracies, but the variability in these effects tends to narrow with more experience with consecutive elections in new democracies (cf.…”
Section: Evaluating Duverger’s Law and The ‘Micro-duvergerian’ Agendamentioning
confidence: 99%
“…Furthermore, Tavits and Annus (2006) emphasized the role of democratic experience in new democracies of Eastern Europe and Russia when they convincingly demonstrated that strategic voting in third-wave democracies tends to increase as voters (but also political elites) become more experienced with the electoral process, the so-called ‘learning hypothesis’ (cf. Tavits and Annus, 2006: 80–87; Maškarinec, 2016). Similarly, Raymond et al (2016) confirmed that the effects of electoral systems and social cleavages significantly differ between emerging and established democracies, but the variability in these effects tends to narrow with more experience with consecutive elections in new democracies (cf.…”
Section: Evaluating Duverger’s Law and The ‘Micro-duvergerian’ Agendamentioning
confidence: 99%